The production and reproduction of prostitution - Petterssoneva Tiby, Tove (Journal of Scandinavian studies in criminology and crime prevention, 2003)
This article is the result of a study aimed at grasping the knowledge of 'prostitution' since 1999 when the purchase of sexual services was criminalised in Sweden. Key informants drawn from the police, social services and voluntary organisations, who work in close proximity to prostitution, were interviewed. We focus on how the position of the informant, considering governmental and non-governmental exercise, effects her or his understanding, and reproduction, of the phenomena. The central themes are the question of definition, the importance of exposure and the occurrence of male prostitution. It is suggested that a study of these themes shows how the traditional position of the bad woman as vendor and the invisible man as purchaser is preserved. Hereby all the other constellations, that may as well be considered to be prostitution, remains unproblematized